Prevalência de anticorpos contra o vírus da diarreia viral bovina em suínos - Gatto, Igor Renan Honorato [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Several species of Pestivirus have pigs as susceptible hosts. The infection of ruminant pestivirus in pigs have been concerning many countries and depending on the diagnosis test used it is hard to differ BVDV from CSFV infections due to serological cross-reaction in diagnostic tests. This study aimed on determining the prevalence of antibodies against bovine viral diarrhea virus (BVDV) in finisher pigs. Prevalence of BVDV -1 and BVDV-2 was investigated and information about the samples origin were analyzed in order to associate the the occurrence of the infection with possible risk factors. The samples were tested using 100 TCID50 and 50 TCID50 and the differences between the titers were analyzed. In addition, differential diagnosis for Classical Swine Fever (CSF) was done in all positive samples. The blood sera samples were obtained from pigs sent to slaughterhouses in the state of São Paulo. The origin of the animals was from farms located in the states of Mato Grosso, Mato Grosso do Sul, Goias, Sao Paulo, Parana, Santa Catarina and Rio Grande do Sul. The samples were tested using the virus neutralization (VN) test according to the Manual of Diagnostic Tests Vaccines for Terrestrial Animals (OIE) and the positive samples were ELISA tested to differ from CSF. 1705 swine serum samples from 33 farms were tested. The VN test showed 5.34% (91 / 1705) of seropositive samples for BVDV, with 3.0% (51 / 1705) for genotype 1 and 2.35% (40 / 1705) for genotype 2. Considering the origin of the samples, the highlights are the states of Mato Grosso, with 10.00% and Rio Grande do Sul, with 9.18% of seropositive for BVDV-1. Regarding to BVDV-2, states that had the highest number of positive samples were Mato Grosso (6.0%) and Mato Grosso do Sul, (4.29%). No significant association was found between risk factors the occurrence of BVDV-1 infection, however, for BVDV-2 positive cases significant associations were found with the risk factors ...

Os suínos são susceptíveis a infecção por diversas espécies de Pestivirus, a infecção de suínos com pestivírus de ruminantes tem gerado preocupação em diversos países, dependendo do método utilizado, o diagnóstico entre BVDV e CSFV pode ser dificultado. O presente trabalho teve como objetivo verificar a prevalência de anticorpos contra o vírus da diarreia viral bovina (BVDV) em suínos terminados. Para tal, foram investigadas as prevalências do BVDV-1 e 2, obtiveram-se informações de prevalência de acordo com a origem das amostras, foram associados fatores de risco à ocorrência da infecção, verificado as diferenças entre os títulos das amostras positivas testadas com 100 TCID50 e 50 TCID50 e realizado diagnóstico diferencial para PSC. Os soros sanguíneo foram obtidos de suínos enviados para matadouros-frigorífico no estado de São Paulo. As propriedades de origem dos suínos eram localizadas nos estados do Mato Grosso, Mato Grosso do Sul, Goiás, São Paulo, Paraná, Santa Catarina e Rio Grande do Sul. As amostras foram submetidas ao teste de VN conforme preconizado pelo Manual of Diagnostic Tests and Vaccines for Terrestrial Animals (OIE), para às sororreagentes, foi realizado o diagnóstico diferencial para PSC pelo método de ELISA. Foram analisadas 1705 amostras de soro sanguíneo de suínos, obtidas de 33 propriedades. O teste de VN indicou 5,34% (91/1705) de amostras sororreagentes ao BVDV, sendo 3,0% (51/1705) para o genótipo 1 e 2,35% (40/1705) para o genótipo 2. Considerando a origem das amostras, destacam-se os estados do Mato Grosso, com 10,00% e Rio Grande do Sul, com 9,18% de amostras sororreagentes ao BVDV-1, contra o BVDV-2, destacam-se os estados do Mato Grosso, com 6,0% e Mato Grosso do Sul, com 4,29% de sororreagentes. Nenhum fator de risco teve associação significativa com a ocorrência de infecção ao BVDV-1, contudo, para o BVDV-2, foram encontradas associações significativas...
Keywords: Suino; Frigorificos; Matadouros; Fatores de risco; Virus; Imunoglobulinas; Risks factors